PERAN ORANG TUA DALAM MENDUKUNG PEMBELAJARAN IPS DI RUMAH PADA SISWA SD - Muhammad Kaulan Karima; Erni, Aprilia Nuraini, Azahra Saputri, Azzahra Andya Khoirunnisa, Delvinia Azizah, Elvanisa Wahyu Az (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This study explores the role of parents in supporting Social Studies (IPS) learning at home for elementary school students. It focuses on how parents contribute as facilitators and motivators in their children's learning during and after the COVID-19 pandemic. Using qualitative descriptive methods, the data were collected through interviews and observations of parents at SDN 1 Rejo Agung. The results show that parental involvement is often situational and depends on school assignments. Various teaching tools such as textbooks, YouTube videos, and real-life examples are utilized. However, challenges such as limited understanding of the subject, time constraints, and lack of access to learning resources hinder the effectiveness. This study recommends enhanced collaboration between schools and parents, and the use of interactive learning media to improve IPS learning outcomes at home.